Representasi Isu Lingkungan dalam Konten Instagram Greenpeace Indonesia - Putri, Sekartaji Anisa (Jurnal Pustaka Komunikasi, 2025)
Various pollution that accompanies increasingly extreme climate change is a problem that must be resolved immediately. Positive content from leading non-profit organizations that invite and inform the public to protect the environment is expected to be a means of raising public awareness. Therefore, it is important to understand the content of social media posts in the form of visual or video uploads from one of the leading non-profit organization's such as Greenpeace Indonesia. This study aims to find out what environmental issues are being raised on Greenpeace Indonesia's Instagram through descriptive content analysis. Content analysis was conducted on Greenpeace Indonesia's Instagram content uploaded in June 2024, totaling 57 contents. The reliability of Krippendorff's alpha in this study was proven to be reliable. In this study, 15 environmental problem themes were found in the content posted by Greenpeace Indonesia on Instagram. Two main themes were found, that is the issue of plastic and environmental conservation efforts. The issue of plastic mostly uploaded in the form of Instagram Posts. In contrast, the issue of environmental conservation mostly uploaded in the form of Instagram Reels.